14-19 Diplomas and Higher Education - Stanley, Julian [Verfasser] (My University, 2010)
"This article describes the involvement of higher education and business in the development of new vocational qualifications for 14-19 year-olds in England. It is intended that this 'co-production' will lead to a set of qualifications which have an 'applied' character and which support progression into both employment and higher education. National availability, strong brand promotion and the inclusion of functional and generic skills are intended to encourage continued participation in education/ training. Relatively low participation in education/training post-16 is perceived as a particular problem in England. The Diploma complements new legislation that requires all 17 years-olds to remain in education or training by 2013 and all 18 year-olds by 2015. The article considers how the facility for progression from Diplomas to university affects the success of the reform and explores possible connections between Diplomas and previously introduced two year vocational degrees in English universities. The article ends with a brief review of how the Diploma reform addresses issues of social inclusion in higher education." (Autorenreferat, BIBB-Doku)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; I 2.2.1 Westeuropa; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Berufliche Qualifikation; Hochschulzugang; England